Blastoid Variant Mantle Cell Lymphoma Expressing Aberrant CD3 and CD10 with Concurrent Small Lymphocytic Lymphoma: Establishment of a Clonal Relationship by B- and T-Cell Receptor Gene Rearrangements - Felten, Christopher L.; Chan, Joel A.; DeCastro, Dulce R.; Lopategui, Jean; Rajurkar, Swapnil P. (Case Reports in Hematology, 2018)
Mantle cell lymphoma (MCL) is an aggressive non-Hodgkin B-cell lymphoma typically expressing CD19, CD20, CD5, FMC-7, CyclinD1, and SOX-11 and harboring the IgH/CCND1 translocation. We report a blastoid variant of mantle cell lymphoma (MCL) involving an inguinal lymph node that, in addition to classical phenotypic and genetic findings, also aberrantly coexpresses surface CD10 and cytoplasmic CD3. Small lymphocytic lymphoma (SLL) was also present in the same lymph node and in the bone marrow. B- and T-cell gene rearrangement studies by PCR show the MCL and SLL to be clonally related. Expression of multiple aberrant antigens and concurrent lymphomas of different classifications can cause a diagnostic challenge. Awareness of such a presentation and integration of the data from morphologic evaluation, flow cytometry, immunohistochemistry, and FISH studies is required for proper diagnosis, prognosis, and therapy.